Real-world multicentre analysis of neoadjuvant immunotherapy and chemotherapy in localized or oligometastatic non-small cell lung cancer (KOMPASSneoOP). (March 2022) - Faehling, Martin; Witte, Hanno; Sebastian, Martin; Ulmer, Matthias; Sätzler, Rainer; Steinestel, Konrad; Brückl, Wolfgang M.; Evers, Georg; Büschenfelde, Christian Meyer zum; Bleckmann, Annalen
Background: Recent clinical trials demonstrate the feasibility of neoadjuvant immuno(chemo)therapy and report high rates of pathological remission, a surrogate marker for overall survival. Patients and methods: This is a retrospective multicentre real-world analysis of patients with locally resectable NSCLC, including oligometastatic disease, who received neoadjuvant immuno(chemo)therapy and resection. Consolidating immunotherapy was applied following multidisciplinary board recommendation. Primary endpoint was the rate of complete pathological response (pCR, no residual vital tumour cells) or major pathological response (MPR, ⩽ 10% residual vital tumour cells). Secondary endpoints included the radiological response and survival. Results: Seven centres contributed 59 patients (56% stage IIB–IIIC, 44% in stage IVA–IVB with up to four oligometastatic sites). MPR was found in 68% including 53% with pCR. There were no radiological progressions. Median follow-up was 24.3 months. At 12 and 24 months, progression-free survival was 82.6% and 68.1%, and overall survival was 89.5% and 87.2%, respectively. Conclusion: To our knowledge, this study encompassed the largest NSCLC real-world cohort treated with neoadjuvant immuno(chemo)therapy to date. In routine clinical practice, resection after neoadjuvant immuno(chemo)therapy is feasible in patients with locally resectable NSCLC, including oligometastatic disease. In line with clinical trials, we found MPR in more than two-thirds of patients. Early data show encouraging survival.